Two new species of Pleurothallidinae (Orchidaceae) from cloud forest remnants in the eastern Andes of Colombia - Gutiérrez Morales, Nicolás; Moreno, Juan Sebastian; Gil-Amaya, Karen; Alegría-Valencia, Melisa (Lankesteriana: International Journal on Orchidology, 2024)
Two new pleurothallid species of the genera Lepanthes and Pleurothallis, native to cloud forest remnants of the Eastern Andes of Colombia, are described and illustrated. Lepanthes pseudoabitaguae is compared with Lepanthes abitaguae, from which it differs by the color of the flowers and by the oblong and biglandular appendix. Pleurothallis falcata is similar to Pleurothallis suspensa, but can be recognized by the falcate to lanceolate leaves, denser inflorescences, longer sepals, and the lip completely recurved with erose apical margins. We also provide comparisons with similar species and offer comments on their ecology. Furthermore, we discuss the significance of this highly anthropized region and its richness in orchid species.